Cefepime-Enmetazobactam: a novel β-Lactam/β-Lactamase inhibitor combination for complicated urinary tract infections - Ramaraj, Arunkumar; Nivasini, Natarajan Thangam; Balaji, Vikram; James, Jerin; Varadarajan, Sathyanarayanan (International Journal of Basic & Clinical Pharmacology, 2025)
Complicated urinary tract infections (cUTIs) represent a significant global health challenge, particularly with the rising prevalence of extended-spectrum β-lactamase (ESBL)-producing pathogens. Cefepime-Enmetazobactam, approved in India in June 2024, represents a novel β-lactam/β-lactamase inhibitor combination specifically developed to address multidrug-resistant Gram-negative infections. This review examines the pharmacological properties, clinical efficacy, and therapeutic potential of Cefepime-Enmetazobactam in managing cUTIs. The Phase 3 ALLIUM trial demonstrated superior clinical cure and microbiological eradication rates compared to Piperacillin-Tazobactam, with particularly pronounced efficacy against ESBL-producing Enterobacterales (73.7% vs 51.5%). The combination exhibits a favourable safety profile with transaminase elevation, increased bilirubin, headache, and infusion site reactions being the most common adverse events. As a carbapenem-sparing option, Cefepime-Enmetazobactam addresses critical antimicrobial stewardship concerns while providing an effective treatment alternative for resistant pathogens. While demonstrating promising results, further research regarding long-term outcomes, resistance development, and cost-effectiveness is warranted to fully establish its role in contemporary antimicrobial therapy.